266 MINIMALLY-EFFECTIVE PHYSICAL ACTIVITY DOSE FOR DEPRESSION AMONG OLDER ADULTS: PRELIMINARY FINDINGS FROM THE IRISH LONGITUDINAL STUDY ON AGEING. (25th October 2022) - Laird, E; Rasmussen, CL; Kenny, RA; Herring, M
Abstract: Background: Among older adults, depression is associated with increased risk of lower physical, social, and cognitive function. Physical Activity (PA) has been associated with lower odds of depression; however, the minimally sufficient dose for protection is unknown. Herein, we quantified the association between different PA doses and depressive symptoms and status among older adults across 10 years (waves 1-5) as part of The Irish Longitudinal Study on Ageing. Methods: PA was measured at each wave using the short-form International Physical Activity Questionnaire (IPAQ-SF). Five dose categories (0, 1-<600, 600-<1, 200, 1, 200-<2, 400 and ≥2, 400 MET.min.week-1) were examined. At all waves, depressive symptoms were assessed using the Center for Epidemiological Studies Depression Scale short form (CES-D) and a score of ≥16 was used to define depression. From Waves 2-5, the Composite International Diagnostic Interview quantified diagnosis of a Major Depressive Episode during the past 12 months, or depression status. Poisson regression quantified associations between PA dose and depressive symptoms and status across time, adjusted for age, health/lifestyle variables and antidepressant medication. Results: Among 4, 017 participants, depression status changed from 8.2% at wave 1 to 12.2% at wave 5. The minimal PA dose associated with lower depressive symptoms was 1-<600 MET.min.week-1 (coefficient = –0.06; 95%CI: –0.10, –0.02; p≤0.003). A dose of 600-<1, 200 MET.min.week-1 was significantly associated with lower odds of depression status (OR = 0.66; 95%CI: 0.50, 0.87; p≤0.004). Other positive predictors associated with lower odds of depression included greater age, higher education status, and sufficient vitamin D status. Conclusion: Present findings suggest that even low physical activity doses appear protective against depressive symptoms among older adults. Moderate PA dose, consistent with WHO recommendations, was protective against major depression over a 10-year period among older adults. However, individuals with chronic conditions may have different PA dose requirements, which should be further investigated.